2015
DOI: 10.1123/jis.2014-0127
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Sport-Based Service Learning Course on Participants’ Attitudes, Intentions and Actions Toward Social Change

Abstract: Framed in the context of a sport-based service learning program that engages in interdepartmental university partnerships (including athletics), the current study focused on addressing the need to analyze the long-term impacts of service learning on students' intentions and actions toward social change. Service learning courses have been shown to facilitate positive outcomes such as increased cultural competency and future intentions toward civic engagement (Bruening et al., 2010, 2014). Building on this knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
(73 reference statements)
1
5
0
Order By: Relevance
“…Specifically, in their study examining the impact of a community-based social marking intervention on recycling behaviors among college football fans, Martin and his colleagues (2015) observed that tailgaters were more receptive to recycling educators who were from their peer group. In addition, in their study on the influence of a sport-based service learning course, Fuller et al (2015) observed how peers provided needed support when some students experienced negative feedback after advocating for social justice. Peer support may be particularly relevant in the intercollegiate sport context, as Taylor (2015) noted how persistent nonsupportive actions displayed by teammates led many athletes to conform to noninclusive athlete archetypes.…”
Section: Meso-level Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, in their study examining the impact of a community-based social marking intervention on recycling behaviors among college football fans, Martin and his colleagues (2015) observed that tailgaters were more receptive to recycling educators who were from their peer group. In addition, in their study on the influence of a sport-based service learning course, Fuller et al (2015) observed how peers provided needed support when some students experienced negative feedback after advocating for social justice. Peer support may be particularly relevant in the intercollegiate sport context, as Taylor (2015) noted how persistent nonsupportive actions displayed by teammates led many athletes to conform to noninclusive athlete archetypes.…”
Section: Meso-level Factorsmentioning
confidence: 99%
“…There is less understanding though, on how to instill the importance of social change in individuals who have not encountered or are not aware of social injustices. However, Fuller et al (2015) provides evidence that participating in perspective-altering experiences, such as a sport-based service learning class, can improve attitudes and increase behaviors related to social justice for all persons-irrespective of one's social status or past experiences. Importantly, the success of the perspective-altering experience is dependent on key factors.…”
Section: Micro-level Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…These scholars investigated social capital development among alumni of a sport-based inner city service learning engagement, and found that the intentional design, management and structure of the program, in line with Sport for Development Theory (Lyras & Welty Peachey, 2011), aided in this development over time. This same group of scholars has a contribution in this special issue (Fuller et al, 2015) as a follow-up to the above referenced work, finding importantly that alumni indicated the service learning experience was critical to helping them recognize social injustices in the world, and that it fostered civic engagement, stimulating future intentions and current involvement in social justice related initiatives. Together, these works are showing that service learning experiences and environments are an important vehicle for creating social change through intercollegiate sport.…”
Section: Sport For Social Change and Intercollegiate Sportmentioning
confidence: 90%
“…In this special issue, contributors build upon the previous work highlighted above and move the study of social change in collegiate sport in intriguing new directions. In addition to Fuller et al (2015) and Cunningham (2015) mentioned above, Taylor provides a personal narrative of his experiences as a college wrestler in a homophobic environment discriminating, more covertly than overtly, against LBGT individuals, and how this motivated and activated him to work for social change by founding Athlete Ally (Taylor, 2015b). Importantly, Taylor calls for leveraging activist activities for LGBT issues to address other aspects of discrimination in sport, such as racism, classism, and sexism.…”
Section: Sport For Social Change and Intercollegiate Sportmentioning
confidence: 99%